THE CONCEPT OF EDUCATION IN THE QUR’AN FOR CHILDREN WITH UNKNOWN PATERNAL IDENTITY: a Thematic Interpretation of The Story of Maryam and Isa As - Sukmana, Jaya; Setyawan, Aris (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2025)
A father's identity is often considered a crucial element in shaping a child’s character and social integrity, whereas the absence of a paternal figure frequently results in stigmatization that impacts the child’s psychological well-being within society. The Qur’an presents the birth of Prophet Isa AS without a father as a divine miracle and simultaneously as a transformative narrative to address social pressure and stigma toward children without known paternal identity. This study aims to explore the educational concept within the Qur’an through the story of Maryam and Prophet Isa as a foundation for instilling spiritual, moral, and social values in children born outside of conventional family structures. Employing a narrative literature review approach and a thematic interpretation strategy (tafsir maudhū‘i), this research analyzes secondary sources including Qur’anic verses, classical and contemporary exegetical texts, and scholarly literature in the fields of Islamic education, child developmental psychology, and social theory. The findings reveal that Maryam’s story embodies values of compassion-based education, spiritual empowerment, and liberation from social stigma, while the figure of Isa represents the potential of a child in a non-ideal context to grow optimally through nurturing rooted in faith and divine values. This article offers a conceptual contribution to the development of an inclusive Islamic educational paradigm that is responsive to diverse family structures and proposes an applied model of Qur’anic interpretation to address contemporary social issues faced by marginalized children.